1969
DOI: 10.1126/science.163.3870.935
|View full text |Cite
|
Sign up to set email alerts
|

Boron Modifications Produced in an Induction-Coupled Argon Plasma

Abstract: Most of the small particles (50 to 100 micrometers in diameter) of microcrystalline beta-rhombohedral boron that quickly transit an argon plasma maintained within a radio-frequency induction-coupled torch emerge as better crystallized spheroids of the same crystalline form and nearly the same size as the starting material. A few crystals of each of four distinctive, well-faceted habits are formed along with the general product. Three of these types are monocrystals of the beta-rhombohedral polymorph, of the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1974
1974
2009
2009

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…[1,110] t-II is also said to have been synthesized by sprinkling finely crushed boron into an argon plasma. [113] Since it has not been possible to reproduce the synthesis of t-II in the form of single crystals and hence its structure determination since 1978, slight doubts about the existence of this modification are justified. According to theoretical calculations, there might be a range over which t-II exists: Hayami and Otani recently published DFT studies on t-I [93] and t-II [114] which suggested that t-I and t-II can be more stable than a-B and b-B if the surface energy is taken into account in the calculations.…”
Section: Synthesis and Controversy As To Their Existencementioning
confidence: 99%
“…[1,110] t-II is also said to have been synthesized by sprinkling finely crushed boron into an argon plasma. [113] Since it has not been possible to reproduce the synthesis of t-II in the form of single crystals and hence its structure determination since 1978, slight doubts about the existence of this modification are justified. According to theoretical calculations, there might be a range over which t-II exists: Hayami and Otani recently published DFT studies on t-I [93] and t-II [114] which suggested that t-I and t-II can be more stable than a-B and b-B if the surface energy is taken into account in the calculations.…”
Section: Synthesis and Controversy As To Their Existencementioning
confidence: 99%
“…[1,110] Außerdem soll t-II durch Einstreuen von fein zerteiltem Bor in ein Argon-Plasma erhalten worden sein. [113] Allerdings ist auch die Synthese von t-II in Form von Einkristallen und die Strukturbestimmung seit 1978 nicht wieder gelungen, sodass auch bei dieser Modifikation Zweifel an der Existenz angemeldet werden könnten. Theoretischen Untersuchungen zufolge soll diese Phase jedoch einen Existenzbereich aufweisen: Kürzlich publizierten Hayami und Otani DFT-Studien zu t-I [93] und t-II, [114] wonach t-I und t-II durchaus stabiler als a-B und b-B sein können, wenn man bei den Rechnungen die Oberflächenenergie berücksichtigt.…”
Section: Tetragonales Bor I Und Ii (T-i T-ii) 231 Synthese Und Kounclassified
“…Approximately 100 liters of waste solution, containing •an estimated 65 g of 234 U; has been concentrated to a volume of eight lit! :!rS wi~h an initial separation from 2 ;bPu and is ready for preparation as feed to the intermediate.purification step.…”
Section: Uranium-234mentioning
confidence: 99%
“…The separation of the two chlorine isotopes, • 3 5 Cl and 3.7Cl, was measured as a f1.1nr.t:ion of time. • Column parameters were derived from the data by fitting to the solution of the differential equation describing the transient performance of the column: ' (2) where w1 is the mass fraction of component 1, t is the time, 11 is the holdup per unit length, and z is the vertical coordinate. The quantities H and K are the initial transport coefficient.…”
Section: S Dropped Below 9dl~mentioning
confidence: 99%